Executive Functioning in Pedophilia and Child Sexual Offending. (17th May 2017) - Massau, Claudia; Tenbergen, Gilian; Kärgel, Christian; Weiß, Simone; Gerwinn, Hannah; Pohl, Alexander; Amelung, Till; Mohnke, Sebastian; Kneer, Jonas; Wittfoth, Matthias; Ristow, Inka; Schiltz, Kolja; et al.
Abstract: Objectives: Pedophilia (P) is a psychiatric disease associated with sexual attraction toward children and often accompanied by child sexual offending (CSO). Consequently, it is important to address the understanding of executive dysfunctions that may increase the probability of CSO. Moreover, this research field has been lacking to disentangle executive deficits associated with pedophilia (as a deviant sexual preference) from those associated with CSO (as a deviant sexual behavior).Methods: The German multi-sided research network NeMUP offers the opportunity to overcome these limitations. By applying the Cambridge Automated Neuropsychological Test Battery in four carefully matched groups of men: (1) pedophiles with ( N =45) and (2) without ( N =45) a history of sexual offending against children; (3) child molesters without pedophilia ( N =19), and (4) non-offending controls ( N =49), we were able to analyze executive functioning in pedophilia and CSO independently.Results: Both CSO groups as compared to both non-CSO groups exhibited worsened response inhibition ability. However, only non-pedophilic offenders showed additionally disabled strategy use ability. Regarding set-shifting abilities, the P+CSO group showed the best performance. We also found that performances were affected by age: only in pedophiles, response inhibition worsened with age, while age-related deficits in set-shifting abilities were restricted to non-pedophilic participants. The latter also differentiated between both sexual preference groups.Conclusions: Our results are the first to demonstrate that executive dysfunctions are related to offense status rather than pedophilic preference. Furthermore, there was evidence for differentiating age and performance correlations between pedophiles and non-pedophiles, which warrants further investigation. ( JINS, 2017, 23, 460–470)